Isolation of Beta-Lactamase from a Penicillin-Susceptible Strain of Staphylococcus aureus - Sachithanandam, S. (1978)
It is generally accepted that strains of Staphylococcus aureus which are susceptible to penicillin G do not produce β-lactamase. However, we have found that such a strain susceptible to 0.06 μg of penicillin per ml and 0.56 μg of methicillin per ml produces β-lactamase(s) which hydrolyzes penicillin G, methicillin, 6-aminopenicillanic acid, and probably cephaloridine. The enzyme which is found only during very early log phase of the growth cycle is not inducible either by penicillin or methicillin and is cell bound and liberated only by disruption of the cell. The rate of enzymatic hydrolysis of methicillin was 60% that of benzylpenicillin. This finding suggests that the elaboration per se of β-lactamase does not necessarily afford resistance to penicillin in this gram-positive-producing cell.